MOTORNO UČENJE - OD TEORIJE DO PRAKSE FIZIČKOG VEŽBANJA - Zoran Milošević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
One of the "problems" that is currently present in physical culture in particular is the issue of relationship between updating - innovations of technology of expert-pedagogical work in all its constitutive forms: physical education, sport, sports recreation etc. Motoric learning in educational process is the polygon of innovations both for the teachers - coaches and students, athletes and those who are involved in sports as recreation. The best evidence to this are the controversial attitudes as well as agreements of the leading psychological theories that analyse the issue of learning within two groups: theory of linking and cognitive theory. The present research focuses on such attitudes that, thanks to their updatedness, contribute to understanding of the problem of transfer of knowledge and motoric skills in the way that does not result with their mutual exclusion but also through narrowing of their problem approach on to typical phases of motoric processing of information that strengthen, namely weaken the established "open loop" (Sheffield), "closed loop" (Adams) and "pattern" (Schmidt) systems vie "attention", "retention", "motivation" and other elements of cognitive processing. Opening up of the issue on application of new but also tested ideas of motoric learning enriches the work on feed back information of subjects of educational process with a clear objective to strengthen the individual and incapacitate it to face its own capacities, knowledge and habits with »motoric problems« in order to start the journey towards the resolving of the same.